Pelatihan Ecoprint: Literasi dan Adaptasi Perubahan Iklim yang Inklusif di Rumah Publik Terpadu YAFSI - Patricia, Angelica; Thamrin, Husni; Utama Ritonga, Fajar (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2024)
Field Work Practice (PKL) is a manifestation of students in applying the knowledge gained when attending lectures so that it aims to improve students' skills in developing mindsets, expressing ideas, and gaining insights to become a skilled and qualified workforce. Practice carried out the second Field Work Practice at the YAFSI Integrated Public House. The problems faced by the members of the YAFSI Integrated Public House are meeting the needs and overcoming the risks of climate change. For this problem, practitioners participate in ecoprint training which is a form of inclusive climate change literacy and adaptation. The author uses the method presented by Kirst-Ashman (2010) regarding the level of social worker practice at the mezzo level, namely the intervention unit is a group with a group work method. As for the results of this second Employment Practice, it is hoped that the group that is the main target of the ecoprint training program becomes a group that can run independently. Ecoprint is one type of batik whose manufacturing method utilizes natural dyes from tannins or dyes of leaves, roots, or stems that are avoided on a piece of cloth and then the cloth is boiled.